2023
DOI: 10.1039/d3sc02348f
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between hydrogen and halogen bonding: substituent effects and their role in the hydrogen bond enhanced halogen bond

Abstract: The Hydrogen Bond Enhanced Halogen Bond (HBeXB) has recently been used to effectively improve anion binding, organocatalysis, and protein structure/function. In this study, we present the first systematic investigation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…It is worth noting that compared with the catalyst E-ET, E-SO performs more sensitively for alcohol oxidation with different substituent groups. It is possibly due to the different substituent groups (including electron-drawing and electron-donating groups) affecting the environment of the H atom, which results in hydrogen bond differences. In addition, to verify the advantage of the encapsulated structure, we compared the oxidation effects of the supported catalysts and encapsulated catalysts. The encapsulated catalysts showed more favorable performance in alcohol oxidation, especially with the SO group modified (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that compared with the catalyst E-ET, E-SO performs more sensitively for alcohol oxidation with different substituent groups. It is possibly due to the different substituent groups (including electron-drawing and electron-donating groups) affecting the environment of the H atom, which results in hydrogen bond differences. In addition, to verify the advantage of the encapsulated structure, we compared the oxidation effects of the supported catalysts and encapsulated catalysts. The encapsulated catalysts showed more favorable performance in alcohol oxidation, especially with the SO group modified (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we also developed the hydrogen bond enhanced halogen bond (HBeXB) which has allowed us to preorganize structure and strengthen XBs by employing complementary intramolecular HBs to the electron-rich belt of XB donors. 54−56 The HBeXB can increase binding by 50fold 57 and our lab and others have used the HBeXB to improve the function of organocatalysts. 58−60 Ho et al have also demonstrated that the HBeXB stabilizes protein folding and enhances the function of a T4 lysozyme derivative.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hydrogen bonding (HB), [1][2][3][4][5][6][7][8] halogen bonding (XB) [9][10][11][12][13][14] and chalcogen bonding (ChB), [15][16][17][18][19][20][21][22] three prominent non-covalent interactions that are weaker than covalent bonds, but can efficiently induce monomer aggregation, have been highly anticipated in self-assembly chemistry over the past two decades. Since the discovery of the double helical structure of DNA by Watson and Crick, 23 chemists have been drawn to design simple linear molecules that are able to form artificial helices.…”
mentioning
confidence: 99%